Optimisation and improvement of police officers’ special rank types (Bulletin of Kharkiv National University of Internal Affairs, 2024)
The article examines the process of reforming the law enforcement system in Ukraine, in particular the creation of the National Police in 2015, and its impact on the rank system of police officers. Special attention is paid to the main changes that occurred as a result of this reform. In particular, such positive aspects as bringing police standards closer to the European level, as well as creating a new police uniform and changing the rank system are highlighted. It is important to note that the reform is aimed at improving the efficiency of law enforcement agencies and their interaction with the public. The article also highlights the problem of the lack of additional ranks and limited career opportunities for junior police officers, which can lead to professional burnout and reduced staff motivation.An analysis of the positive experience of using the extended rank of junior and sergeant ranks in countries such as Canada, Germany, Greece, Spain, as well as the states of Virginia and Delaware in the USA is conducted. The proposed ways of solving the shortcomings in the rank system are aimed at improving the working conditions and motivation of the police personnel. In addition, it is proposed to introduce new ranks for junior and non-commissioned officers of the police in order to stimulate further self-development of professional skills and career growth prospects. In addition, each new rank will have separate duties and functions that will facilitate mutual assistance and cooperation with other police officers. It is also important to emphasise the need to update the design for cadets of higher education institutions with specific learning conditions and lyceums.